Analisis Kebijakan Industri Gula Indonesia - Wayan R. Susila; Bonar M. Sinaga (Jurnal Agro Ekonomi, 2005)
EnglishIn the last decade, Indonesian sugar industry has faced some inter-related problems that have caused a setback of the industries.  Besides inefficiency in farm and plant levels, the declining performance of the industry has been attributed to the inappropriate government policies related to international trade and domestic support. In response to these problems, this study is aimed at evaluating and formulating alternative government policies related to international and domestic market policies. The method used is policy simulation analysis based on econometric model of Indonesian sugar market. The results of this study show that under heavily distorted international market of sugar, policies directly related to farm gate price are more effective in affecting some aspects of Indonesian sugar industry. In this respect, provenue price policy is more effective than tariff-rate quota, import tariff, and input subsidy. Sugar cane smallholders in general are more responsive toward government policies, compared to government-owned estates, and private estates. Policy implication of this study is that to create a fairer playing ground, Indonesian sugar industry still needs some government supporting policies. Provenue price, tariff-rate quota, import tariff, input subsidy, are policies that can be used to achieve the goal. IndonesianPada dekade terakhir, industri gula Indonesia sedang mengalami berbagai masalah yang saling terkait yang mengakibatkan kemunduran industri tersebut. Di samping masalah inefisiensi di tingkat usahatani dan pabrik, penurunan kinerja itu juga disebabkan oleh kebijakan yang kurang memadai, baik kebijakan domestik maupun kebijakan perdagangan internasional. Dalam upaya mengatasi masalah tersebut, penelitian ini bertujuan untuk  mengevaluasi kebijakan pemerintah serta merumuskan alternatif kebijakan yang terkait. Metode yang digunakan adalah simulasi kebijakan dalam suatu model ekonometrik industri gula domestik. Hasil studi menunjukkan bahwa dalam situasi perdagangan yang distortif, kebijakan yang berkaitan langsung dengan harga output lebih efektif dibandingkan kebijakan yang berkaitan dengan input, guna mendukung pengembangan industri gula Indonesia. Kebijakan harga provenue lebih efektif bila dibandingkan dengan tariff-rate quota, tarif impor, dan subsidi input.  Terhadap kebijakan pemerintah, perkebunan tebu rakyat lebih responsif dibandingkan dengan perkebunan milik negara dan perkebunan swasta.  Implikasi kebijakan dari penelitian ini adalah dalam menciptakan medan persaingan yang lebih adil, industri gula Indonesia masih memerlukan dukungan kebijakan pemerintah. Kebijakan harga provenue, impor tarif, tariff-rate quota, dan subsidi input merupakan beberapa pilihan kebijakan guna pengembangan industri gula Indonesia.